Oil Prices and Stock Markets during the 2014–16 Oil Price Slump: Asymmetries and Speed of Adjustment in GCC and Oil-Importing Countries. Issue 15 (7th December 2020) - Siddiqui, Anjum; Mahmood, Haider; Margaritis, Dimitris
ABSTRACT: We assess the effect of the oil price slump of 2014–2016 on the stock markets of the GCC countries and the four largest oil importers: China, Japan, India, and South Korea. We find that compared to the pre-slump period negative oil price changes had larger effects on equity prices in oil exporting countries, whereas positive oil price innovations had larger effects on oil importers. We also observed intertemporal symmetry switching in GCC countries and an increase in the speed of adjustment of equity prices during the slump for both oil importers and exporters from which we infer a time varying relationship between oil and equity prices.